Pelatihan Pemberdayaan Masyarakat Nelayan Di Pesisir Pantai Desa Toniku Jailolo Selatan - Sandi Rais; Lita Asyriati Latif; Bambang Tjiroso (Patria Artha Journal of Community (PKM), 2022)
This community service program aims to empower and train the community in Toniku Village about processing anchovies and salted fish that are clean and hygienic in terms of health, providing solutions on how to process fish drying quickly with modern methods. The target of the implementation of this program is the entire fishing community, both those who have fishing boats and fish rompon as well as labor fishermen as an effort to improve the standard of life of fishermen both economically, socio-culturally and in improving the field of knowledge (education), in order to further develop anchovy production. quality and fast drying time of fish. The results of the implementation of this program are that there are 3 recommendations for improvement, including; The fish drying method uses traditional methods and the drying process is too long, so a fish drying device design and an anchovy size filter are needed which is done manually with a sieve, so it is necessary to design an anchovy size filter to assist fishermen.